French Vividness of Olfactory Imagery Questionnaire: A Potential Tool for Diagnosing Olfactory Loss by Assessing Olfactory Imagery? - Fantin, Luca; Ceyte, Hadrien; Ramdane-Cherif, Zhor; Jacquot, Muriel; Hossu, Gabriela (Frontiers in Psychology, 2020)
Several studies have shown a significant relationship between smelling and olfactory imagery abilities. The primary aim of the present study was to validate a French version of the Vividness of Olfactory Imagery Questionnaire (VOIQ). The secondary aim was to investigate its capability to differentiate individuals with smell loss from healthy individuals. After having elaborated a French translation of the VOIQ (fVOIQ), we evaluated olfactory imagery abilities of 387 French participants who anonymously self-completed the fVOIQ: 121 pathologic individuals (hyposmic and anosmic), 244 normosmic individuals (healthy non-expert), and 22 fragrance experts. Significant split-half reliability as expressed by Spearman correlation coefficients for the global sample, as well as for each group separately, indicated the excellent internal consistency of the fVOIQ. Moreover, results revealed a significant effect of the smelling ability group on fVOIQ score, suggesting that daily olfactory stimulation is fundamental to maintaining the ability to create a vivid image and that severe loss of smell may result in progressive impairment of olfactory imagery. Our fVOIQ and the original English version seemingly have similarly high benefit in differentiating experts and normosmic individuals based on their olfactory imagery ability. Moreover, the fVOIQ seems capable of differentiating individuals with loss of smell from healthy individuals. These findings demonstrate the reliability and validity of the fVOIQ, and its capability to differentiate individuals’ smelling ability according to their olfactory imagery ability.